Effect of GuizhiShaoyaoZhimuTang (桂枝芍药知母汤）and its components on the LFA-1 mediated leukocyte adhesion to ICAM-1. - Lau, Jasmine Cai Ying. (2012)
GuizhiShaoyaoZhimuTang (GSZT) is a prescription from the ‘Synopsis of the Golden Chamber’ that is used in treatment of Rheumatoid Arthritis (RA). RA is characterized by the chronic inflammation of the joints. Inflammation is dependent on many mechanisms, one of them being LFA-1/ICAM-1 interaction that causes white blood cell adhesion and eventually, white blood cell recruitment and extravasation that aggravates the inflammation of the joints in RA. GSZT is proposed to play a role in the inhibition of LFA-1/ICAM-1 in its effect in mediating the inflammation in RA. Using cell adhesion assays, SKW-3 T-cells expressing high affinity LFA-1 were incubated in the presence of the drug in a microtitre plate with wells coated with ICAM-1 ligands. Our results show that GSZT and some of its individual herbs and powders do play a role in the inhibition of LFA-1/ICAM-1 interaction, one pathway that could explain GSZT’s effectiveness as a treatment for RA.